Stabilized electrode

By covering the carbon coating on the ion sieve electrode material, the problem of insufficient stability of electrode materials in aqueous solution in the prior art is solved, and the efficiency and stability of lithium ion extraction is achieved, the life of the electrode material is extended, and the tolerance to other sodium ions, calcium ions and magnesium ions is improved.

JP2024511802A5Pending Publication Date: 2025-04-02LEIBNIZ INSTITUT FUR NEUE MATERIALIEN GMBH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023559681
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-01
Filing Date
2022-03-24
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

The prior art In extracting lithium ions, the stability of the electrode material is insufficient, especially in aqueous solutions, resulting in low lithium ion extraction efficiency and short electrode material life.

Method used

An ion sieve covered with a carbon coating is used as the electrode material, which can effectively adsorb and release lithium ions in a liquid medium, improving the stability and tolerance of the electrode.

Benefits of technology

The ion sieve electrode material covered by carbon coating significantly improves the stability and efficiency of lithium ion extraction, extends the service life of the electrode material, and improves the tolerance to other sodium ions, calcium ions and magnesium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode material for extracting elemental ions from a liquid medium, comprising at least one electrode material comprising at least one ion sieve capable of retaining or releasing elemental ions, or a mixture of such ion sieves, wherein the ion sieve(s) is / are coated with carbon.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode material for extracting elemental ions from a liquid medium. [Background technology]

[0002] The expected surge in the use of mobile electronics and electric vehicles powered by lithium-ion batteries has resulted in a surge in the demand for lithium-ion based rechargeable energy storage. It is predicted that 5 million tonnes of lithium, more than one-third of the total lithium reserves available on land, will be consumed between 2015 and 2050, and lithium reserves may be exhausted by 2080. Currently, most lithium is extracted from brines due to the relatively low cost and abundant reserves compared to mineral resources. There is a great demand for low-cost, environmentally friendly methods that can produce lithium quickly and in large quantities. There are many methods to extract lithium from brines, such as solar evaporation, adsorption, and electrolysis. The solar evaporation method is the most widespread, but it is time-consuming and space-consuming. The adsorption method requires large amounts of acid for regeneration, and the electrolysis process suffers from relatively low lithium recovery efficiency and membrane fouling. Therefore, there is a need to develop advanced, sustainable, and effective lithium recovery technologies.

[0003] Electrochemical processes are particularly promising for lithium extraction due to the process simplicity, energy efficiency, and high lithium selectivity. A 1993 study by Kanoh et al. introduced λ-MnO2 (lithium extraction) and Pt (O2 generation) as electrodes for lithium extraction (Non-Patent Document 1). In 2012, Pasta et al. introduced a new cell concept in which lithium iron phosphate (LiFePO4) and silver act as the cathode and anode, respectively (Non-Patent Document 2). In this cell, one cycle includes two half-cycle processes of capture and release. During charging, lithium and chloride ions are captured by iron phosphate and silver, respectively, and during discharge, the ions are released from the electrodes into the solution. In the following years, the results of many studies on lithium extraction from brine have been reported, and in almost all cases the procedure is based on LiFePO4 due to the high selectivity and green production process of LiFePO4. For example, Trocoli et al. (Non-Patent Document 3) reported the use of cells with LiFePO4 and NiHCFe as electrodes for lithium extraction from brine in the Atacama, increasing the lithium concentration in the feedwater from 4% to 11% with an energy consumption of 8.7 Wh / mol. - / I3 - Using polydopamine-coated LiFePO4 and Pt immersed in lithium as electrodes, the cells achieved a more than 4000-fold increase in Li / Na ion selectivity (Non-Patent Document 4). In these studies, the stability of the electrons was hardly investigated. Also, the cations present in addition to lithium, such as Na + , Ca 2+ , and Mg 2+ It is also not known whether this will adversely affect the stability of LiFePO4.

[0004] However, efficient use of electrodes, especially for water treatment, requires higher cycling stability in addition to lower capacity fade, and the stability of known electrode materials is insufficient for this. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Kanoh, H.; Ooi, K.; Miyai, Y.; Katoh, S., Electrochemical recovery of lithium ions in the aqueous phase. Separation Science and Technology 1993, 28, (1-3), 643-651. [Non-Patent Document 2] Pasta, M.; Battistel, A.; La Mantia, F., Batteries for lithium recovery from brines. Energy & Environmental Science 2012, 5, (11), 9487 [Non-Patent Document 3] Trocoli, R.; Battistel, A.; La Mantia, F., Nickel hexacyanoferrate as suitable alternative to Ag for electrochemical lithium recovery. ChemSusChem 2015, 8, (15), 2514-2519 [Non-Patent Document 4] Kim, J.-S.; Lee, Y.-H.; Choi, S.; Shin, J.; Dinh, H.-C.; Choi, JW, An electrochemical cell for selective lithium capture from seawater. Environmental Science & Technology 2015, 49, (16), 9415-9422 Summary of the Invention [Problem to be solved by the invention]

[0006] It is an object of the present invention to identify electrode materials that have improved stability, especially for use in aqueous solutions, as well as the use of such electrode materials and methods for water treatment. [Means for solving the problem]

[0007] The above object is achieved by the invention having the features of the independent claims. Advantageous developments of the invention are characterized in the dependent claims. The wording of all claims is incorporated by reference into the content of this specification. The invention also encompasses all reasonable combinations, in particular all enumerated combinations of the independent and / or dependent claims.

[0008] The present invention relates to an electrode material for extracting elemental ions from a liquid medium, comprising at least one electrode material comprising at least one ion sieve capable of intercalating or releasing elemental ions, or a mixture of such ion sieves, wherein the ion sieve(s) is / are coated with carbon.

[0009] The electrode material is surprisingly suitable for CDI (capacitive deionization) or FDI (faradaic deionization).

[0010] Surprisingly, it has been found that such a coating of the ion sieve significantly increases the stability of the ion sieve and therefore also that of the electrode material without any extraction losses. The coating also improves the tolerance of other cations in the liquid medium, such as potassium, sodium or magnesium ions.

[0011] The extraction is preferably a desalting, in particular a CDI or FDI.

[0012] Desalination here means that ions from the medium surrounding the electrode undergo intercalation within the electrode.

[0013] In a preferred embodiment, the elemental ion is a lithium ion.

[0014] The ion sieve may be in the form of a depleted ion sieve (delithiated ion sieve in the case of lithium) or a lithium intercalated ion sieve. In the lithium intercalated form, it is preferably a lithium-containing metal oxide, which may also be a composite oxide or a lithium-containing metal phosphate. It is preferably a composite oxide containing lithium and at least one further element selected from Co, Mg, Cr, Mn, Ni, Fe, Al, Mo, V, W or Ti. LiNiO2, LiCoO2, LiMn2O4, LiNi 0.34 Mn 0.33 Co 0.33 O2, or lithium iron phosphate or a mixture thereof.

[0015] Lithium iron phosphate, LiMn2O4 or a mixture thereof is preferred. Lithium iron phosphate is LiFePO4, Li x Me y FePO4, LiFeMe y PO4, or mixtures thereof, Me is Mn, Co, Mo, Ti, Al, Ni, Nb, or mixtures thereof, 0 <x<1かつ0<y<1である。

[0016] Depending on the application, it may be necessary to convert the ion sieve from the lithium intercalated form to the depleted form.

[0017] The lithium intercalating ion sieve is coated with a carbon layer. This layer is preferably obtained by carbonization, in particular by carbonization of alkyl esters and in particular crosslinked polyalkyl esters. The preferred electrode materials here are LiFePO4 / C, Li x Me y FePO4 / C and LiFe x Me y PO4 / C, in particular LiFePO4 / C. Carbonization gives a thin and at the same time permeable layer. The layer preferably comprises graphitic carbon. The carbon may be completely graphitic.

[0018] A layer thickness of at least 2 nm (measured by TEM) is preferred.

[0019] The coated ion sieve is preferably at least 10 mm 2 The carbonization is preferably carried out using the lithium intercalated form.

[0020] In a preferred embodiment, the ion sieve is in the form of particles, preferably having a maximum dimension of 2 μm, preferably 1 μm (measured by TEM), more preferably 700 μm. The minimum dimension of the particles is independently at least 10 nm, in particular at least 20 nm.

[0021] The ion sieve is preferably in crystalline form.

[0022] In a preferred embodiment, the particles are coated with a carbon layer.

[0023] The present invention also relates to an electrode for extracting elemental ions from a liquid medium, comprising as electrode material at least one ion sieve capable of intercalating or releasing elemental ions, or a mixture of such ion sieves, wherein the ion sieve(s) is / are coated with carbon.

[0024] The electrode may also include further elements, such as a carrier material or a matrix material.

[0025] The liquid medium is preferably water. The at least one ion sieve is preferably an ion sieve as described for the electrode.

[0026] The present invention also relates to a method for extracting elemental ions using at least one electrode material of the invention. The elemental ions are preferably lithium ions.

[0027] The individual method steps are described in more detail herein below. The steps do not necessarily have to be performed in the order described, and the methods described may also have additional steps that are not mentioned.

[0028] In this way, the intercalation and release of elemental ions can be controlled by applying a specific voltage. This allows the elemental ions to be selectively extracted from the surrounding medium, especially water, and also released back into the medium. If this occurs in different media, it is possible to deplete the elemental ions in one medium and release them in the other. For example, this allows the elemental ions to be selectively depleted, especially from an aqueous medium. The intercalation and release here corresponds to a cycle that is repeated many times.

[0029] The carbon coating allows the intercalation capacity of the electrode to decrease much less than would occur without the coating, which certainly makes it possible to economically use the ion sieves of the present invention in such processes.

[0030] The lithium intercalated ion sieve is coated with a carbon layer. This layer is preferably obtained by carbonization, in particular of alkyl esters and in particular of crosslinked polyalkyl esters. Carbonization can preferably be achieved by coating the ion sieve in an ester and then carbonizing at a temperature above 600°C. The ion sieve is preferably dispersed in a mixture of hydroxyl compounds and carboxylic acids and is preferably heated, after formation of the ester, to above 100°C, preferably from 101°C to 300°C, in particular from 150°C to 250°C, preferably to 200°C, to remove any water that may be present. After 1 to 5 hours, the mixture is heated to above 500°C, preferably from 501°C to 900°C, in particular from 550°C to 800°C, very in particular from 600°C to 800°C, very in particular from 700°C. This is preferably carried out for more than 4 hours, preferably from 4 to 7 hours. This carbonization, preferably both heat treatments, is carried out under low oxygen, preferably oxygen-free conditions, preferably under an inert gas such as nitrogen or argon. The mass ratio of the ion sieve to the mixture of hydroxyl compounds and carboxylic acids is preferably between 3:1 and 1:3, preferably between 2:1 and 1:2, very preferably between 1.2:1 and 1:1.2, in particular between 1.1:1 and 1:1.1. The hydroxyl compounds and carboxylic acids are preferably compounds with a molecular mass of less than 400 g / mol. The hydroxyl compounds can be used here in excess relative to the carboxylic acids, based on the ratio of hydroxyl groups to carboxylic acid groups. Preferred hydroxyl compounds are alcohols, such as methanol, ethanol, propanol, butanol, diols, such as ethylene glycol, propane-1,3-diol, polyethylene glycol, butane-1,4-diol, pentane-1,5-diol, octane-1,8-diol, and triols such as glycerol, preferably alcohols, in particular diols, having two or more hydroxyl groups.

[0031] Examples of carboxylic acids preferably containing 1 to 24 carbon atoms are monocarboxylic acids (e.g., formic acid, acetic acid, propionic acid, butyric acid, pentanoic acid, hexanoic acid, capric acid, stearic acid, phenylacetic acid, benzoic acid), polycarboxylic acids having two or more carboxyl groups (e.g., oxalic acid, malonic acid, adipic acid, succinic acid, glutaric acid, phthalic acid, trimesic acid, trimellitic acid), unsaturated carboxylic acids (e.g., acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, and oleic acid), and hydroxycarboxylic acids (e.g., glycolic acid, lactic acid, malic acid, and citric acid).

[0032] The combination of one or more carboxylic acids having two or more carboxylic acid groups and, in particular, a hydroxyl compound having two or more hydroxyl groups is preferred. This gives a crosslinked polyester compound as an intermediate, which is then carbonized, and the combination of a tricarboxylic acid, such as citric acid, and, in particular, a diol, such as ethylene glycol, is particularly preferred. The carboxylic acid is preferably used in anhydrous form.

[0033] For the formation of the ester, it may be necessary to heat the composition up to 100° C., preferably up to 90° C., in particular from 30° C. to 100° C., in particular from 50° C. to 90° C. This treatment is preferably carried out for at least 1 hour, in particular for at least 2 hours, preferably from 1 hour to 10 hours, preferably from 2 hours to 8 hours, in particular from 3 hours to 5 hours. This treatment gives an ion sieve coated with the ester.

[0034] Other catalysts such as metal compounds, e.g. ferrocene, can also be used, however this is not preferred.

[0035] This carbonization results in a particularly homogeneous, thin and highly porous carbon layer on the ion sieve.

[0036] In one embodiment, the present invention provides a method for selectively extracting lithium from an aqueous solution and recovering and concentrating lithium in a salt brine, comprising the steps of: a) providing an apparatus comprising a cell for containing a salt brine and filling the cell with the salt brine; b) placing a conductive substrate coated with an ion sieve in the cell and placing a further conductive substrate in the cell, wherein at least one of the two conductive substrates and (during the process) the ion sieve are coated with Li + and Depending on the method steps and the nature of the conductive substrate used, the method steps may differ with regard to the replacement of the salt brine and the division of the cell into subcells, optionally separated by membranes. This is especially true when the additional conductive substrate is not an ion sieve but a chemically neutral electrode such as activated carbon. This allows the construction of the cell to be simplified.

[0037] The electrodes can preferably be used in cells for capacitive deionization (CDI), in particular in through-flow cells.

[0038] In one embodiment, the present invention provides a method for selectively extracting lithium from an aqueous solution and recovering and concentrating lithium in a salt brine, comprising the steps of: a) providing an apparatus for electrodialysis comprising an electrodialysis cell, dividing the electrodialysis cell into a lithium salt chamber and an alkaline chamber by means of an anion exchange membrane, filling the alkaline chamber with a salt brine and filling the lithium salt chamber with a supporting electrolyte solution, for example a solution of NaCl, KCl, NH4Cl, Na2SO4, K2SO4, NaNO3 or KNO3; b) placing a conductive substrate coated with a depletion ion sieve in the alkaline chamber to act as a cathode and a conductive substrate coated with a lithium intercalate ion sieve in the lithium salt chamber to act as an anode, wherein at least one, preferably both, of the two conductive substrates comprises the ion sieve of the present invention as an electrode material, and during the electrodialysis, the ion sieve is charged with Li in the alkaline chamber for conversion into another lithium intercalate ion sieve under an external potential. +The lithium-intercalated ion sieve can be subjected to Li intercalation to transform into another ion sieve under an external potential. + The Li can be released into the conductive solution by the depletion ion sieve and the lithium intercalation ion sieve. + After each of the intercalation and desorption of the lithium salt, concentration occurs in the lithium salt chamber to obtain a lithium-enriched solution; The present invention relates to a method comprising the steps of:

[0039] After step 2), in the alkaline chamber, Li + undergoes intercalation into the ion sieve, thereby being converted into a lithium intercalated ion sieve, and in the lithium salt chamber, the lithium intercalated ion sieve is converted into Li + into the conductive solution and is converted into an ion sieve. Thus, the two electrodes can be reused by reversing their positions.

[0040] Thus, step 2) can be followed by the steps of draining the liquid from the alkaline chamber after lithium intercalation, refilling the alkaline chamber with salt brine, reversing the positions of the cathode and anode, and continuing the electrodialysis.

[0041] Optionally, after step 2), in order to avoid reversing the positions of the cathode and anode, the following step may be carried out to deposit Li + from other cations, Li + can be concentrated by: maintaining the positions of the cathode and anode, draining the liquid from the alkaline chamber after lithium intercalation, transferring the lithium solution from the lithium salt chamber to the alkaline chamber, and refilling the lithium salt chamber with salt brine, i.e., switching the functions of the alkaline chamber and the lithium salt chamber, and continuing the electrodialysis. Thus, the above process is repeated, switching the functions of the alkaline chamber and the lithium salt chamber.

[0042] When the electrode is made to function as an ion sieve, it is preferable to employ only the electrode material of the present invention therein in order to achieve high stability of the electrode over many cycles. This achieves better extraction of lithium. 2+ , Ca 2+ , or Na + The presence of other cations such as are also better tolerated.

[0043] The salt brine is selected from a solution containing lithium ions, a primary salt brine, an evaporated salt brine, an evaporated salt brine after potassium extraction, or a mixture thereof. The salt brine may be a liquid from geothermal energy production or a similar process liquid.

[0044] The conductive substrate is a ruthenium coated titanium mesh, a graphite plate, a platinum group metal or alloy foil, a carbon fabric, or a graphite foil.

[0045] The process parameters are as follows: solution temperature: 0℃~80℃; pH: 2~12; and voltage between two electrodes: 0.5V~2V.

[0046] In one embodiment of the present invention, the concentration of oxygen dissolved in the medium is preferably reduced during intercalation of elemental ions. This is preferably achieved by purging the medium with a non-oxidizing gas, preferably nitrogen, which drives oxygen out of the medium. The reduction in oxygen content further enhances the stability of the electrodes. This process can also be employed to enhance the cycling stability of uncarbonized ion sieves.

[0047] The present invention therefore also relates to a method for extracting elemental ions from a liquid medium, the liquid medium comprising the electrode material described according to the present invention, even if the material does not have a carbon layer, the oxygen content of the medium being reduced by purging with a non-oxidizing gas, which gas is preferably nitrogen. The method is preferably carried out using the electrode material of the present invention.

[0048] The present invention also relates to an apparatus for carrying out the method of the present invention, comprising at least one electrodialysis cell divided into a lithium salt chamber and an alkaline chamber by an anion exchange membrane, at least one cathode and at least one anode, the cathode and the anode being respectively arranged in the two chambers, the cathode and the anode comprising the corresponding form of the ion sieve of the present invention as electrode material.

[0049] A further aspect of the present invention comprises the use of the ion sieve of the present invention in a process for the extraction of elemental ions from a liquid medium, preferably an aqueous medium, especially water.

[0050] A further aspect of the present invention includes the use of an electrode of the present invention in a process for extracting elemental ions from a medium, preferably an aqueous medium.

[0051] Particularly suitable as media for extracting elemental ions, in particular lithium, are industrial wastewaters or process liquids such as battery recycling liquids or rinsing liquids, or wastewaters from the mining industry, such as mineral waters. The media can also be liquids obtained from boreholes, for example from hot water sources, or from geothermal energy production or heat pumps.

[0052] Further details and features are evident from the following description of preferred exemplary embodiments in conjunction with the dependent claims. Each feature can be realized alone or in combination with one another. The options for achieving the objectives are not limited to the exemplary embodiments.

[0053] Thus, for example, a given range always includes all unmentioned intermediate values ​​and all possible subintervals.

[0054] Exemplary embodiments are illustrated diagrammatically in the figures, in which identical reference signs in the individual figures indicate identical or functionally identical elements or elements which correspond to one another in terms of their functionality. [Brief description of the drawings]

[0055]

Figure 1

Figure 2

Figure 3

Figure 4

Figure 5

Figure 6

Figure 7

Figure 8

Figure 9

[0056] Materials and Methods Synthesis of LiFePO4 and LiFePO4 / C, and preparation of electrodes 16m 2 Commercially available LiFePO4 (Sued-Chemie) with a specific surface area of ​​10 ... The alkyl ester coating was then carbonized in two heating steps in argon: first, the sample was heated to +200 °C for 2 h to remove the moisture in the material, and then the sample was heated to +700 °C and kept at this temperature for 6 h to obtain the LiFePO4-carbon hybrid.

[0057] Electrodes were fabricated by mixing and grinding the active material (LiFePO4 or LiFePO4 / C), acetylene black, and polyvinylidene fluoride (Sigma-Aldrich) in 1-methyl-2-pyrrolidinone (Sigma-Aldrich) in a mass ratio of 8:1:1 to form a slurry. The slurry was applied to graphite paper (SGL, 300 μm thick) with a doctor blade (200 μm thick) and left overnight at room temperature in a hood. The electrodes were then dried in a vacuum oven at +80 °C for 24 h.

[0058] Electrochemical measurements The electrochemical behavior of LiFePO4 and LiFePO4 / C was investigated in a custom-made cell with a three-electrode system. Electrodes with a diameter of 12 mm made of LiFePO4, LiFePO4 / C or activated carbon electrodes (YP-80F, Kuraray) were used as working electrodes (LiFePO4, LiFePO4 / C) or counter electrodes (activated carbon). The electrodes were arranged in a sandwich and separated in the cell body by a glass fiber mat (diameter 13 mm, GF / A, Whatman). An Ag / AgCl reference electrode (3M KCl, BASi) was attached laterally to the cell body. Before the tests, the assembled cells were filled with various electrolytes. For single salt electrolytes, 1M LiCl, 1M MgCl2, 1M CaCl2, and 1M NaCl were used. For mixed salt electrolytes, 5mM LiCl and 50mM MeCl were used. X (Me=Na, Ca, Mg, and X corresponds to the Me charge) was used.

[0059] The cells were connected to a VSP300 potentiostat / galvanostat (Bio-Logic) and cyclic voltammograms were applied against Ag / AgCl with a scan rate of 0.1 mV / s and cutoff potentials from -0.4 V to +0.8 V. Potential-limited galvanostatic charge-discharge measurements were carried out to test the performance stability of LiFePO4 and LiFePO4 / C. Prior to electrochemical operations, the electrolyte was continuously purged with nitrogen gas for 1 h to remove dissolved oxygen in the electrolyte (only when investigating the effect of oxygen). The dissolved oxygen concentrations after gas purging are shown in Table 2.

[0060] Additionally, to prevent the lithium concentration in the electrolyte from increasing as a result of the LiFePO4 and LiFePO4 / C charging process, the electrodes were delithiated prior to electrochemical testing. To delithiate the electrodes, they were charged in a three-electrode system in 1M LiCl electrolyte at a current of 0.1 A / g and a cutoff voltage of +0.4 V vs. Ag / AgCl. Electrochemical impedance spectroscopy (EIS) measurements were performed at formal potentials in the frequency range of 1 MHz to 10 MHz at an excitation voltage of 5 mV vs. Ag / AgCl.

[0061] The conductivity of LiCl, MgCl2, CaCl2, and NaCl at various concentrations was tested using a microcell electrochemical HC cell (RHD Instruments) with Pt electrodes and a ModuLab electrochemical workstation (Solartron Analytical). 0.9 mL of each electrolyte was added to the measuring cup by syringe, and then the Pt electrode crucible was closed. Thermally conductive paste (Eurotherm 2000) was employed in the center of the closed cell and the base unit to improve the heat transfer between them. The potentiostatic impedance at each temperature was measured after the temperature was stabilized for 10 minutes. The impedance was measured at various temperatures from +10°C to +60°C and +25°C at open circuit potential (OCV) from 1 Hz to 3 MHz with Δ10°C increments. The conductivity and activation energy values ​​were calculated according to Eqs. 1 and 2.

number

number

[0062] Lithium selectivity experiments Lithium extraction experiments were carried out in a multichannel cell, filled with glass fiber mats (GF / A, Whatman) and sealed with an anion exchange membrane (FAS-PET-130, Fumatech) (area = 6.76 cm). 2Two water channels were fabricated through a 1000-m thick PET glass tube (thickness = 500 μm). A LiFePO4 or LiFePO4 / C electrode was placed at the end of the channel and in contact with a graphite current collector. Prior to the experiments, one electrode was delithiated by the method described above. The channel with the pretreated electrode is referred to as "Channel 1" and the other as "Channel 2."

[0063] A 10-liter tank containing LiCl (10 mM) was used as the water supply at a flow rate of 3 mL / min, while a constant current (40 mA / g) was applied at a cell voltage of -0.4 V to +0.4 V using a VSP300 potentiostat / galvanostat system. Throughout the experiment, the electrolyte was continuously purged with N2 gas to remove dissolved oxygen. The mass of the electrode was 8 mg, and the changes in conductivity and pH of the two channels were recorded online by a conductivity sensor (Metrohm, PT1000) and a pH sensor (WTW SensoLyt 900P), respectively. Lithium was extracted throughout the cycle, and the lithium removal capacity and energy consumption of the cell in one cycle were calculated accordingly according to Equation 3 and Equation 4.

number

number

[0064] To investigate the selectivity and stability of LiFePO4 and LiFePO4 / C, we used an electrolyte containing 5 mM LiCl and 50 mM NaCl with a volume of 10 L. The outlet of channel 2 was connected to an inductively-coupled plasma optical emission spectrometer (ICP-OES, ARCOS FHX22, SPECTRO Analytical Instruments) to quantify the concentration changes of cations. The mass of the electrode was about 18 mg, and a low specific current of 30 mA / g and a flow rate of 1.2 mL / min were used to amplify the ICP signal. Calibration curves were constructed according to the correlation between the intensity of each wavelength and the concentration of the solution (Figures 7A and 7B). The measured intensities from the extracted samples were converted into concentration profiles. Since the charge-discharge process had a reverse course and the possibility of energy recovery was negligible, the amount of extracted lithium and the energy consumption were calculated according to Equation 5 and Equation 6 in a half cycle to evaluate the performance of LiFePO4 and LiFePO4 / C.

number

number

[0065] Material characterization The surface morphology of LiFePO4 and LiFePO4 / C was investigated by scanning electron microscope (JEOL JSM 7500F) at 1 kV. X-ray diffraction measurements were carried out on a D8 Advance Diffractometer (Bruker AXS) equipped with a copper X-ray source (Cu-Kα, 40 kV, 40 mA) and a Goebel mirror with a point focus (0.5 mm). Raman spectra were recorded on a Renishaw inVia system using a Nd:YAG laser with an excitation wavelength of 532 nm. The spectral resolution was 1.2 cm. -1 The diameter of the laser spot on the sample was about 2 μm, and the total power consumption was 0.2 mW.

[0066] Characterization of LiFePO4 and LiFePO4 / C FIG. 1A shows a transmission electron micrograph of LiFePO4. The LiFePO4 particles are typically about 300 nm long and 150 nm wide. Lattice bands with a typical spacing of 0.34 nm to 0.35 nm aligned with the (111) and (021) planes of LiFePO4 are discernible at higher resolution (FIG. 1B). LiFePO4 / C shows the ubiquity of carbon coating the LiFePO4 particles (FIGS. 1C and 1D).

[0067] FIG. 1E shows the X-ray diffraction patterns of LiFePO4 and LiFePO4 / C. The diffraction pattern of LiFePO4 / C is the same as that of LiFePO4, which is identified as the orthorhombic phase (PDF 81-1173), indicating that the carbon coating process does not destroy the inherent structure of LiFePO4. FIG. 1F shows the Raman spectra of LiFePO4 and LiFePO4 / C. -1 The band at 1338 cm is due to the symmetric stretching of the PO bond in LiFePO4. -1 and 1598 cm -1 The peaks correspond to the D and G bands of carbon, respectively. The D band (disordered peak) corresponds to the A 1g The vibrational mode is the G band (graphite peak), which is the E band of C-C bond stretching. 2gThus, both commercial LiFePO4 and LiFePO4 / C show the presence of incomplete graphitic carbon, with carbon being the minority phase in the former case.

[0068] Lithium extraction from LiFePO4 in 10 mM LiCl aqueous solution The Li removal capacity of LiFePO4 in 10 mM LiCl aqueous solution was quantified. When a specific current of 30 mA / g is applied during charging, the conductivity of channel 1 decreases and that of channel 2 increases (Figure 2A). This corresponds to the reduction of the cathode with lithium uptake and the oxidation of the anode with the release of lithium into the feed water stream (Eq. 7). The reverse process is observed during the discharge process. The lithium extraction capacity of the cell does not decrease over 24 cycles, with an average capacity of 79 ± 6 mg / l. LiCl / electrode, 13±1mg Li / electrode (Fig. 2B), suggesting that LiFePO4 is stable in 10 mM LiCl degassed aqueous solution. The average energy consumption of the cell is 3 Wh / mol LiCl and 3Wh / mol Li is equivalent to. Li 1-x FePO4+xLi + +xe - =LiFePO4 formula 7

[0069] Effect of other cations compared to lithium LiFePO4 + Cyclic voltammetry was performed to investigate the selectivity behavior towards ZnO in comparison with other cations. This was done by comparing the electrochemical performance in various single cation electrolytes. As shown in Figure 3A, Figure 3B, and Figure 3C, a pair of redox peaks occurs in all electrolyte types. The measured peak current was lowest when 1 M CaCl2 aqueous electrolyte was used. With 1 M LiCl, the redox peak current is highest and the peak potential is shifted to a more positive range compared to the other electrolytes, which can be attributed to the contribution of lithium in the solution leaching out of the electrode.

[0070] To further quantify the potential shift, the formal potential (E 1 / 2 As shown in Table 3, the formal potential in LiCl solution decreases with decreasing concentration. During the charging process (the first electrochemical process during cyclic voltammetry), the Li in LiFePO4 + is released into the electrolyte. Therefore, in tests in electrolytes containing other cations such as NaCl, MgCl2, or CaCl2, the cyclic voltammograms and formal potentials are nearly identical.

[0071] To reduce the loss of additional lithium ions from the electrode to the electrolyte and to compare electrolytes with different concentrations, the LiFePO4 electrode was delithiated before galvanostatic charge-discharge tests. A significant decrease in the initial capacity of LiFePO4 was observed in all electrolytes (Figures 3D and 3E). The capacity was + and Na + The decrease was the slowest in the mixed solution of Ca 2+ The capacity in the 5 mM LiCl+50 mM MgCl2 solution first increases and then decreases, and this increase is due to the trace amount of MgCl. 2+ This can be attributed to the intercalation of Mg 2+ However, Mg intercalates easily into the structure of LiFePO4. 2+ and Li + Both intercalations are not completely reversible, and as a result, the capacity continues to decrease. To investigate why the capacity of the LiFePO4 electrode decreases during cycling, we performed post-mortem X-ray diffraction patterns of delithiated LiFePO4 after 100 charge-discharge cycles in various electrolytes.

[0072] In addition to the effect on stability, Li +Cations other than 10 ... ct ) The diagonal lines at low frequencies represent the Warburg impedance (W1) corresponding to the diffusion of lithium ions. R ct The values ​​of Ca and W1 are calculated according to the simulated circuit as shown in Table 1. 2+ and Mg 2+ has a negative effect on the charge transfer process, and R ct The values ​​are 38.7 Ω cm 2 and 37.3 Ω cm 2 which is the R of pure 5 mM LiCl. ct Value (20.1 Ω cm 2 ) is almost twice as high as that of 5 mM LiCl and 50 mM NaCl. ct The value is the R for pure LiCl electrolyte. ct The effect of other cations on the Warburg impedance is similar to that of R ct Following the pattern observed in the values ​​of Mg 2+ and Ca 2+ The Warburg impedance of an electrolyte containing Na + The impedance of the electrolyte is higher than that of the electrolyte containing LiCl and pure LiCl. This result indicates that the diffusion of lithium ions into the liquid side is more difficult in the former electrolyte than in the latter electrolyte. The different effects are due to the different conductivities of the cations.

[0073] As can be seen in FIG. 4A, LiFePO4 is not completely delithiated, so the delithiated LiFePO4 is composed of heterosites FePO4 and LiFePO4. This result is consistent with the Raman data (FIG. 8). Raman measurements were performed at two randomly selected points, and the peak at point 1 (952 cm) was -1), which is consistent with the Raman spectrum of LiFePO4 (Figure 1F). Elsewhere, the observed peaks correspond to FePO4. After 100 cycles in 5 mM LiCl, some diffraction peaks, such as 37.4° 2θ (the (211) plane of the heterosite FePO4), disappear, indicating the destruction of the structure of FePO4. 2+ A different behavior is observed for the FePO-containing electrode after 100 cycles, where the diffraction peak at 18.13°2θ corresponding to the (020) plane of the heterosite FePO4 disappears, indicating a significant capacity loss. Figure 4B shows the Raman spectra of the electrode after 100 cycles in various electrolytes. After charging and discharging in NaCl, LiCl, and CaCl2 electrolytes, the peak at 488 cm -1 (Li cage / PO4 3- Asymmetric bending), 596 cm -1 (PO4 3- Asymmetric bending, ν4), 652cm -1 (PO4 3- Asymmetric bending of , ν2, and 691 cm -1 The peak at is not obvious, indicating the breakage of PO bonds, which is another reason for the degradation of the performance of LiFePO4, i.e., the loss of oxygen species.

[0074] Effect of oxygen content in the electrolyte The effect of oxygen content on the stability of LiFePO4 was investigated using a mixed electrode containing 5 mM LiCl and 50 mM NaCl as the feed water. The spur of this choice was due to the observation that sodium ions have the lowest effect on the stability of LiFePO4. First, we tested the stability of LiFePO4 at 100 mA / g in the potential range of -0.4 V to +0.5 V vs. Ag / AgCl in a 5 mM LiCl + 50 mM NaCl solution that was continuously purged with O2 and N2 before the electrochemical process. After 100 cycles, LiFePO4 retains 69% of its initial capacity in the N2-purged electrolyte, while the capacity retention values ​​in the O2-purged and untreated electrolytes are 43% and 52%, respectively (Figure 5A). This suggests that dissolved O2 in the electrolyte significantly accelerates the loss of performance of LiFePO4.

[0075] The effluent solution was continuously analyzed by online monitoring using inductively coupled plasma optical emission spectroscopy (ICP-OES). As shown in Figures 5B, 5C, and 5D, LiFePO4 retains good selectivity for lithium throughout, regardless of oxygen content. Similar to the specific capacity trend (Figure 5A), LiFePO4 tested in feedwater with continuous N2 purge was the most stable, with 70% capacity retention after 10 cycles (Figure 5E). The lithium extraction capacity is only about half of the initial value in feedwater without any treatment and is slightly higher than in feedwater with continuous O2 purge. At higher oxygen content, the capacity decreases with increasing amplitude. Li + In contrast to the extraction / recovery capacity of LiFePO4, the energy consumption remains stable for 10 cycles, as shown in Figure 5F. This result indicates that the oxygen content has little effect on the energy consumption of the system, but has a large effect on the structural and chemical stability of LiFePO4 itself.

[0076] X-ray diffraction was used to investigate how dissolved oxygen in the electrolyte affects the stability of LiFePO4. This confirmed the structural changes of the electrode material after 100 cycles in an electrolyte consisting of 5 mM LiCl and 50 mM NaCl (Figure 9). Unlike the powder-only measurements, the cast electrodes showed strong reflections from the graphite paper (26.5°2θ and 54.6°2θ), so the diffraction patterns were normalized to peaks not related to the graphite foil. Compared to the LiFePO4 and LiFePO4 electrodes, all electrodes showed two additional peaks at 31.7°2θ and 45.5°2θ, corresponding to the (200) and (220) planes, respectively, after 100 cycles, which are associated with the presence of highly symmetric phases (residual salts). Electrodes cycled in electrolytes with less dissolved oxygen (N2 purged) show lower peak broadening compared to samples with O2 purged. It appears that higher amounts of dissolved oxygen lead to greater degradation of the LiFePO4 material.

[0077] Improved stability of LiFePO4 with carbon coating To increase the stability of LiFePO4, a layer of carbon was bonded to LiFePO4 to prevent oxygen attack. Figure 6A shows the difference between LiFePO4 and LiFePO4 / C in 1M LiCl aqueous solution. As can be seen, the capacity of LiFePO4 / C decreases slightly from 115mAh / g to 95mAh / g after 100 cycles, retaining 83% of the initial capacity. In comparison, LiFePO4 without carbon coating retains only 30% of the initial capacity after 100 cycles, decreasing from 92mAh / g to 27mAh / g. The performance at lower concentrations (5mM LiCl+50mM NaCl) is similar (Figure 6B). LiFePO4 / C still has 85% of the capacity at the first cycle (41mAh / g and 48mAh / g), while LiFePO4 only retains 52% of its initial value.

[0078] FIG. 6C shows the X-ray diffraction patterns of LiFePO4 / C and LiFePO4 electrodes after testing in 1M LiCl and 5 mM LiCl+50 mM NaCl.

[0079] To further investigate whether the carbon coating can improve the stability of LiFePO4 during lithium extraction, the performance of LiFePO4 / C in 10 mM LiCl and 5 mM LiCl + 50 mM NaCl solutions (continuous N2 purge) was tested using a rocking chair cell. Similar to LiFePO4, LiFePO4 / C also shows good selectivity for lithium (Figure 6D). However, LiFePO4 / C has a higher lithium extraction capacity (17.8 mg / g electrode in the first cycle) as shown in Figure 6E. Li Compared to 21.0 mg per gram of electrode Li), and has better stability, with a retention rate of 82% after carbon coating. The higher capacity of LiFePO4 / C is attributed to the carbon coating improving the electronic conductivity of LiFePO4 (Li, J.; Qu, Q.; Zhang, L.; Zhang, L.; Zheng, H., A monodispersed nano-hexahedral LiFePO4with improved power capability by carbon-coatings. Journal of alloys and compounds 2013, 579, 377-383), i.e., the active material is fully available at high currents. In addition, the carbon layer is highly resistant to oxygen and OH. - (He, P.; Liu, J.-L.; Cui, W.-J.; Luo, J.-Y.; Xia, Y.-Y., Investigation on capacity fading of LiFePO4in aqueous electrolyte. Electrochimica Acta 2011, 56, (5), 2351-2357). Moreover, the additional carbon present in nanohybridized form in LiFePO4 / C could effectively reduce the resistance of LiFePO4 and lower the energy consumption (Figure 6F). The average energy consumption of LiFePO4 / C in 10 cycles was 3.0 ± 0.5 Wh / mol. Li It is.

[0080] The effects of cations and dissolved oxygen on the stability of LiFePO4 were investigated in symmetric cells (i.e., LiFePO4 and LiFePO4 pairs). + , Mg 2+ , and Ca 2+ Li in the brine + Cations other than Ca affect the stability and electrochemical properties of LiFePO4. 2+ has the most adverse effect, while Na + shows no obvious effect in the potential range from -0.4 V to +0.8 V. The stability and electrochemical properties of LiFePO4 are2+ Dissolved oxygen similarly exacerbates the fading of LiFePO4. Reducing the dissolved oxygen concentration (N2 purging) dramatically increases the capacity retention over 10 cycles in 5 mM LiCl + 50 mM NaCl from 47% to 70%. After carbon coating, the retention further increases to 82% with an energy consumption of 3.0 ± 0.5 Wh / mol. Li These two methods improve the performance stability of LiFePO4 as a material for lithium extraction. Although lowering the dissolved oxygen may not be practical for to-scale applications, carbon coating of LiFePO4 is a simple and very promising approach for large-scale use.

[0081] [Table 1]

[0082] [Table 2]

[0083] [Table 3]

[0084] References Kanoh, H.; Ooi, K.; Miyai, Y.; Katoh, S., Electrochemical recovery of lithium ions in the aqueous phase. Separation Science and Technology 1993, 28, (1-3), 643-651. Pasta, M.; Battistel, A.; La Mantia, F., Batteries for lithium recovery from brines. Energy & Environmental Science 2012, 5, (11), 9487. Trocoli, R.; Battistel, A.; La Mantia, F., Nickel hexacyanoferrate as suitable alternative to Ag for electrochemical lithium recovery. ChemSusChem 2015, 8, (15), 2514-2519. Kim, J.-S.; Lee, Y.-H.; Choi, S.; Shin, J.; Dinh, H.-C.; Choi, J. W., An electrochemical cell for selective lithium capture from seawater. Environmental Science & Technology 2015, 49, (16), 9415-9422. Ma, Z.; Fan, Y.; Shao, G.; Wang, G.; Song, J.; Liu, T., In situ catalytic synthesis of high-graphitized carbon-coated LiFePO4 nanoplates for superior li-ion battery cathodes. ACS Applied Materials & Interfaces 2015, 7, (4), 2937-2943. Li, J.; Qu, Q.; Zhang, L.; Zhang, L.; Zheng, H., A monodispersed nano-hexahedral LiFePO4 with improved power capability by carbon-coatings. Journal of alloys and compounds 2013, 579, 377-383. He, P.; Liu, J.-L.; Cui, W.-J.; Luo, J.-Y.; Xia, Y.-Y., Investigation on capacity fading of LiFePO4 in aqueous electrolyte. Electrochimica Acta 2011, 56, (5), 2351-2357.

[0085] That is, the present invention provides the following electrode materials. Item 1. An electrode material for extracting elemental ions from a liquid medium, comprising at least one electrode material containing at least one ion sieve capable of intercalating or releasing elemental ions, or a mixture of such ion sieves, wherein the ion sieve(s) is / are coated with carbon. Item 2. The electrode material according to Item 1, wherein the elemental ions are lithium ions. Item 3. The electrode material according to Item 1 or 2, wherein the ion sieve after incorporation of the elemental ions is a lithium-containing metal oxide or a lithium-containing metal phosphate. Item 4. The electrode material according to Item 3, wherein the ion sieve is a composite oxide containing lithium and at least one further element selected from Co, Mg, Cr, Mn, Ni, Fe, Al, Mo, V, W or Ti, or lithium iron phosphate. Item 5. The lithium iron phosphate is selected from LiFePO 4 , Li x Me y FePO 4 , LiFeMe y PO 4 , or a mixture thereof, where Me is Mn, Co, Mo, Ti, Al, Ni, Nb, or a mixture thereof, and 0 < x < 1 and 0 < y < 1. The electrode material according to Item 4. Item 6. The electrode material according to any one of Items 1 to 5, wherein the carbon layer is obtained by carbonization. Item 7. The electrode material according to any one of Items 1 to 6, wherein the ion sieve is in the form of particles. Item 8. An electrode for extracting elemental ions from a liquid medium, comprising the electrode material according to any one of Items 1 to 7. Item 9. A method for extracting elemental ions from a liquid medium using at least one electrode material according to any one of Items 1 to 7, wherein the intercalation and release of the elemental ions are controlled by applying a voltage. Item 10. a) Prepare an electrodialysis apparatus equipped with an electrodialysis cell, divide the electrodialysis cell into a lithium salt chamber and an alkali chamber using an anion exchange membrane, fill the alkali chamber with brine, and fill the lithium salt chamber with a supporting electrolyte solution. b) placing a conductive substrate coated with a depletion ion sieve in the alkaline chamber to act as a cathode and a conductive substrate coated with a lithium intercalate ion sieve in the lithium salt chamber to act as an anode, wherein at least one of the two conductive substrates, preferably both, comprises the ion sieve according to any one of claims 1 to 7 as an electrode material, and during the electrodialysis, the ion sieve is charged with Li in the alkaline chamber for conversion into another lithium intercalate ion sieve under an external potential. + and the lithium intercalated ion sieve can be subjected to Li intercalation to undergo transformation into another ion sieve under the external potential. + into a conductive solution, and Li is released from the depletion ion sieve and the lithium intercalation ion sieve. + After each of the intercalation and desorption of the lithium salt, concentration occurs in the lithium salt chamber to obtain a lithium-enriched solution; The method according to claim 9, comprising: Section 11. 11. The method according to item 9 or 10, characterized in that the concentration of oxygen dissolved in the medium is reduced during the intercalation of the elemental ions, preferably by purging the medium with nitrogen. Section 12. An apparatus for carrying out the method according to any one of items 9 to 11. Section 13. 8. Use of the electrode material according to any one of items 1 to 7 in a process for extracting elemental ions from a liquid medium. Section 14. 1. A method for extracting elemental ions from a liquid medium using at least one ion sieve, wherein the intercalation and release of said elemental ions is controlled by applying a voltage and the concentration of oxygen dissolved in said medium is reduced by purging said medium with a non-oxidizing gas.

Claims

1. 1. An electrode material for extracting elemental ions from a liquid medium, comprising at least one electrode material comprising at least one ion sieve capable of intercalating or releasing elemental ions, or a mixture of such ion sieves, wherein the ion sieve(s) is / are coated with carbon.

2. 2. The electrode material according to claim 1, wherein the elemental ion is a lithium ion.

3. 3. The electrode material according to claim 1 or 2, characterized in that the ion sieve after the incorporation of the elemental ions is a lithium-containing metal oxide or a lithium-containing metal phosphate.

4. 4. The electrode material according to claim 3, characterized in that the ion sieve is a composite oxide containing lithium and at least one further element selected from Co, Mg, Cr, Mn, Ni, Fe, Al, Mo, V, W or Ti, or lithium iron phosphate.

5. The lithium iron phosphate is LiFePO 4 , Li x Me y FePO 4 , LiFeMe y P.O. 4 5. The electrode material according to claim 4, wherein Me is Mn, Co, Mo, Ti, Al, Ni, Nb, or a mixture thereof, and 0<x<1 and 0<y<1.

6. 6. An electrode material according to claim 1, characterized in that the carbon layer is obtained by carbonization.

7. Electrode material according to any one of claims 1 to 6, characterized in that the ion sieve is in the form of particles.

8. An electrode for extracting elemental ions from a liquid medium, comprising an electrode material according to any one of claims 1 to 7.

9. 8. A method for extracting elemental ions from a liquid medium using at least one electrode material according to any one of claims 1 to 7, wherein the intercalation and release of said elemental ions is controlled by applying a voltage.

10. a) providing an apparatus for electrodialysis comprising an electrodialysis cell, the electrodialysis cell being divided into a lithium salt chamber and an alkaline chamber using an anion exchange membrane, the alkaline chamber being filled with a salt brine and the lithium salt chamber being filled with a supporting electrolyte solution; b) placing a conductive substrate coated with a depletion ion sieve in the alkaline chamber to act as a cathode and a conductive substrate coated with a lithium intercalate ion sieve in the lithium salt chamber to act as an anode, wherein at least one of the two conductive substrates comprises the ion sieve according to any one of claims 1 to 7 as an electrode material, and during the electrodialysis, the ion sieve is charged with Li in the alkaline chamber for conversion into another lithium intercalate ion sieve under an external potential. + and the lithium intercalated ion sieve can be converted to another ion sieve under the external potential by Li + into a conductive solution, and Li by the depletion ion sieve and the lithium intercalation ion sieve + After each of the intercalation and desorption of the lithium salt, concentration occurs in the lithium salt chamber to obtain a lithium-enriched solution; 10. The method of claim 9, comprising:

11. a) providing an apparatus for electrodialysis comprising an electrodialysis cell, dividing the electrodialysis cell into a lithium salt chamber and an alkaline chamber using an anion exchange membrane, filling the alkaline chamber with a salt brine and filling the lithium salt chamber with a supporting electrolyte solution; b) placing a conductive substrate coated with a depletion ion sieve in the alkaline chamber to act as a cathode and a conductive substrate coated with a lithium intercalating ion sieve in the lithium salt chamber to act as an anode, both of the two conductive substrates comprising the ion sieve according to any one of claims 1 to 7 as electrode materials, during the electrodialysis, the ion sieve is capable of intercalating Li + in the alkaline chamber for conversion to another lithium intercalating ion sieve under an external potential, and the lithium intercalating ion sieve is capable of releasing Li + into a conductive solution for conversion to another ion sieve under the external potential, and after the intercalation and release of Li + by the depletion ion sieve and the lithium intercalating ion sieve, respectively, concentration takes place in the lithium salt chamber to obtain a lithium concentrated solution; 10. The method of claim 9, comprising:

12. A method according to any one of claims 9 to 11, characterized in that the concentration of oxygen dissolved in the medium is reduced during the intercalation of the elemental ions.

13. The method of claim 12, wherein the concentration of oxygen dissolved in the medium is reduced by purging the medium with nitrogen.

14. Apparatus for carrying out the method according to any one of claims 9 to 13.

15. Use of the electrode material according to any one of claims 1 to 7 in a process for the extraction of elemental ions from a liquid medium.

16. 1. A method for extracting elemental ions from a liquid medium using at least one ion sieve, wherein the intercalation and release of said elemental ions is controlled by applying a voltage and the concentration of oxygen dissolved in said medium is reduced by purging said medium with a non-oxidizing gas.